Antarctic Ardley Island terrace — An ideal place to study the marine to terrestrial succession of microbial communities - Nopnakorn, Potjanicha; Zhang, Yumin; Yang, Lin; Peng, Fang (Frontiers in Microbiology, 2023)
Chronosequences study are effective tools to study the effects of environmental changes or disturbances on microbial community structures, diversity, and the functional properties of ecosystems. Here, we conduct a chronosequence study in the Ardley Island coastal terrace of the Fildes Peninsula, Maritime Antarctica. The results revealed that prokaryotic microorganisms changed orderly among the 6 successional stages. Some marine microbial groups could still be found in near-coastal soils of the lowest stratum. Animal pathogenic bacteria and stress-resistant microorganisms occurred at the greatest level with the longest succession period. Through Adonis analysis (PERMANOVA), soil elements Mg, Si, and Na can be used to better explain the changes of prokaryotic microorganisms along terrace, which may be the main driving factors of the microbial communities assembly over the succession. Environmental factors, on the other hand, also play an important role in the succession of microbial communities, which could be different among each microorganism. The succession of bacterial communities is greatly affected by pH and water content; archaeal communities are greatly affected by 〖NH〗_4^+; fungal communities are affected by nutrients such as 〖NO〗_3^-. In the analysis of the characteristic microorganisms along terrace, it is found that the succession of microorganisms may be influenced by more complex and comprehensive factors, such as environmental instability, relationship with plants and ecological niches, and environmental tolerance. We found that budding reproduction and/or with filamentous appendages bacteria were enriched in lowest stratum, which might be connected to its tolerance to rapid changes and barren environments. In addition, the decline in ammonia oxidation capacity of Thaumarchaeota archaeade with succession and the evolution of the fungi-plant relationship throughout classes were revealed. Overall, this research contributes to a better knowledge of how microbial communities have changed over time after marine–to–terrestrial transition of the Ardley Island terrace. It represents as an ideal place to study the succession of microbial communities. These findings will lay the foundation for more in-depth research regarding microbial adaptations and evolutionary mechanisms throughout the marine-terrestrial transition in the future.